SOME EDUCATIONAL CASE ASSIGNMENTS THAT ARE USED TO TEACH SUBJECTS OF ELEMENTS OF FUNCTIONAL ANALYSIS - Akbarov Ummatali Yigitaliyevich; Isaboyeva Dilyoraxon (Galaxy International Interdisciplinary Research Journal, 2022)
In given clause the tasks of problem training of the module elements of the functional analysis and creation modern didactical materials are considered. The typical examples from didactical of materials such as the non-standard tests and cases are given. Some scientific - methodical conclusions are made.